Hokusai a graphic biography - Latanza, Giuseppe; Matteuzzi, Francesco 1978- (Laurence King Publishing, 2021)
"A stunning visual biography of one of Japan's most famous historical artists, this book beautifully illustrates the story of Katsushika Hokusai. Enter the world of Katsushika Hokusai - the enigmatic creator of Japanese art's all-time most iconic image. This vivid graphic biography tells the story of Hokusai's intriguing life and pioneering works, details the fascinating historical context of Edo-era Japan, and explains how Hokusai forged an image of his country that still resonates across the world today. Telling the story of both his eccentric (and incredibly productive) life - while simultaneously painting a fascination picture of his wider cultural legacy, this book is ideal for both those new to Hokusai's work - and his biggest fans."--Provided by publisher
Translated from the Italian
Keywords: Katsushika, Hokusai -- 1760-1849; Katsushika, Hokusai / 1760-1849 / Comic books, strips, etc; Painters / Japan / Biography; Painters / Japan / Comic books, strips, etc; Printmakers / Japan / Biography; Printmakers / Japan / Comic books, strips, etc; Ukiyoe / History / Comic books, strips, etc; Painting / Japan / History / Comic books, strips, etc; Prints, Japanese / Comic books, strips, etc; Katsushika, Hokusai / 1760-1849; Ukiyoe; Prints, Japanese; Painting; Painters; Printmakers; Japan; History; Historical comics; Graphic novels; Biographies; Biographical comics; Comics (Graphic works); Biografie; Comic